The first cyanomethyl complex of gold, synthesized by reaction of a AuI complex with acetonitrile in the presence of a new guanidine N-superbase - Emeljanenko, Dimitri; Peters, Anastasia; Vitske, Viktoriia; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
Herein we report on the synthesis of the new strong N-base and electron donor tdmegb [1,2,4,5-tetrakis(N,N′-dimethylethyleneguanidino)benzene]. Compared to the previously synthesized ttmgb [1,2,4,5-tetrakis(tetramethylguanidino)benzene], this compound turned out to be a slightly better electron donor and a slightly weaker base. In experiments in which [AuCl(PPH3)] was dissolved in CH3CN together with tdmegb, we observed the formation of the first cyanomethyl complex of Au, namely [Au(CH2CN)(PPh3)] in good yield. This reaction does not take place for ttmgb. Moreover, in CH2Cl2 solutions containing the three components [AuCl(PPh3)], tdmegb and a nitrile (in large excess), only AuI reduction leading to a [Au11Cl3(PPh3)7] cluster is observed. Possible reaction mechanisms for this unusual reaction are discussed.
Im Titel ist "I" bei "AuI" hochgestellt
Gesehen am 13.03.2023